Pembangunan Kakas Bantu untuk memberikan Rekomendasi Perbaikan Kalimat Kebutuhan yang Ambigu menggunakan Teknik Berbasis Aturan dan Statistik - Dino Keylas; Denny Sagita Rusdianto; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Software Requirements Specification (SRS) is a document that contains list of software requirements. The statement of software requirements is written in natural language, so it is possible contains ambiguous words. Those condition can cause misinterpretation by software developer. One result that can be caused is that the software produced not in accordance with what user required. This research proposes a method to detection ambiguity of software requirements statement in computationally using rule-based techniques and statistical-based technique. Rule-based techniques are used to justify whether a requirements sentence is ambiguous or unambiguous based on a repository of rules and recommendations that have been compiled. Statistics based techniques used to provide repairing recommendations for ambiguous software requirements statement. The output of this research is the case tool used to detect and provide recommendations for improvements of software requirements statement. The input from the case tool is SRS document. Based on the testing of system performance validation, utility tool can do the detection process and provide recommendations for software requirements statement in less than 120 seconds.